2022
DOI: 10.3390/v14112574
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization and an Evolutionary and a Pathogenicity Analysis of Reassortment H3N2 Avian Influenza Virus in South China in 2019–2020

Abstract: Seasonal H3N2 influenza virus has always been a potential threat to public health. The reassortment of the human and avian H3N2 influenza viruses has resulted in major influenza outbreaks, which have seriously damaged human life and health. To assess the possible threat of the H3N2 avian influenza virus to human health, we performed whole-genome sequencing and genetic evolution analyses on 10 H3N2 field strains isolated from different hosts and regions in 2019–2020 and selected representative strains for patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…In addition, the internal genes underwent frequent reassortment with multiple subtypes. In general, the internal genes of H3N2 AIVs are similar to those of H1, H4, H5, H6, H7, H10, and H11 subtypes viruses (Figure 2), which are commonly detected in poultry farms and in LPMs [19][20][21]. Genes of H9 subtype viruses were found to be clustered into the same groups formed by the PB2, PA, NP, M, and NS genes of H3N2 AIVs (Figures In summary, the internal genes of the H3N2 AIVs were clustered into groups containing genes from as many as 12 HA subtype viruses, namely, H1, H2, H4, H5, H6, H7, H8, H9, H10, H11, H12, and H14 subtype viruses.…”
Section: Phylogeneticmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the internal genes underwent frequent reassortment with multiple subtypes. In general, the internal genes of H3N2 AIVs are similar to those of H1, H4, H5, H6, H7, H10, and H11 subtypes viruses (Figure 2), which are commonly detected in poultry farms and in LPMs [19][20][21]. Genes of H9 subtype viruses were found to be clustered into the same groups formed by the PB2, PA, NP, M, and NS genes of H3N2 AIVs (Figures In summary, the internal genes of the H3N2 AIVs were clustered into groups containing genes from as many as 12 HA subtype viruses, namely, H1, H2, H4, H5, H6, H7, H8, H9, H10, H11, H12, and H14 subtype viruses.…”
Section: Phylogeneticmentioning
confidence: 92%
“…The H3N2 subtype has been the main subtype circulating in avian species in China [18], and has undergone active reassortment with other influenza virus subtypes in live poultry markets (LPMs) [19][20][21][22], which could generate a virus with pandemic potential. We previously showed that H3N2 AIVs isolated from LPMs have complicated gene constellations, and some isolates can transmit among guinea pigs and ferrets [20].…”
Section: Introductionmentioning
confidence: 99%
“…The time to the most common ancestor was evaluated using the BEAST package (v1.8.4) with the GTR-F-R4 nucleotide substitution model for HA sequences and the GTR-F-R3 nucleotide substitution model for NA sequences and by choosing the appropriate clock model. Markov chain Monte Carlo runs 50 million states with sampling every 5,000 steps, ensuring an effective sample size of more than 200 [26,27]. Each tree ran three times independently and was combined by Log Combiner.…”
Section: Model Selection and Evolutionarymentioning
confidence: 99%
“…After a burn-in of 10%, the final tree was summarized using TreeAnnotator. The tree was summed using TreeAnnotator and embellished in FigTree (v1.4.4) software [27].…”
Section: Model Selection and Evolutionarymentioning
confidence: 99%
“…Currently, we are dealing in Africa as elsewhere globally, with a tripledemic of SARS CoV-2 Omicron numerous sub-variants, respiratory syncytial virus (RSV), and several influenza viruses including novel 1 and potential reassortment influenza subtypes’ infection 2 , 3 , 4 . The clinical manifestations of these and other respiratory viral infections are mostly similar 5 especially when the patients are seeking an early medical advice as we highly recommended and continue to recommend to be noted that the vast majority of our African patients can't afford to perform any investigations due to economic reasons and again we had to adjust our practice to best serve all patients.…”
Section: Dear Editormentioning
confidence: 99%